Reference standard space hippocampus labels according to the European Alzheimer's Disease Consortium–Alzheimer's Disease Neuroimaging Initiative harmonized protocol: Utility in automated volumetry. Issue 8 (23rd February 2017) - Wolf, Dominik; Bocchetta, Martina; Preboske, Gregory M.; Boccardi, Marina; Grothe, Michel J.
Abstract: Introduction: A harmonized protocol (HarP) for manual hippocampal segmentation on magnetic resonance imaging (MRI) has recently been developed by an international European Alzheimer's Disease Consortium–Alzheimer's Disease Neuroimaging Initiative project. We aimed at providing consensual certified HarP hippocampal labels in Montreal Neurological Institute (MNI) standard space to serve as reference in automated image analyses. Methods: Manual HarP tracings on the high‐resolution MNI152 standard space template of four expert certified HarP tracers were combined to obtain consensual bilateral hippocampus labels. Utility and validity of these reference labels is demonstrated in a simple atlas‐based morphometry approach for automated calculation of HarP‐compliant hippocampal volumes within SPM software. Results: Individual tracings showed very high agreement among the four expert tracers (pairwise Jaccard indices 0.82–0.87). Automatically calculated hippocampal volumes were highly correlated (rL/R  = 0.89/0.91) with gold standard volumes in the HarP benchmark data set ( N  = 135 MRIs), with a mean volume difference of 9% (standard deviation 7%). Conclusion: The consensual HarP hippocampus labels in the MNI152 template can serve as a reference standard for automated image analyses involving MNI standard space normalization.